Integrin Adhesions Suppress Syncytium Formation in the Drosophila Larval Epidermis - Wang, Yan (2015)
Funding Information: We thank members of M.J.G.’s lab for comments; Jodie Polan for confocal assistance; Guy Tanentzapf, Andreas Wodarz, and Talila Volk, for fly stocks/antibodies; the Bloomington Drosophila Stock Center, the Vienna Drosophila RNAi Center, and the Kyoto stock center for fly strains; and the Developmental Studies Hybridoma Bank for antibodies. This work was supported by a March of Dimes Basil O’Connor Award (5-FY06-588) and NIH R01 GM083031 to M.J.G., NIH R01 GM084103 to J.L.K., and European Research Council Starting Grant (2007-StG-208631) to A.J. Publisher Copyright: © 2015 Elsevier Ltd. All rights reserved.